Oxidation of the cyanobactin precursor peptide Is independent of the leader peptide and operates in a defined order - Gao, S; Ge, Y; Bent, A; Schwarz-Linek, U; Naismith, J (American Chemical Society, 2018)
The five-membered nitrogen plus heteroatom rings known as azolines or in their oxidized form as azoles are very common in natural products and drugs. The oxidation of thiazoline to thiazole in the cyanobactin class of natural products is one of the several important transformations that are known to alter the biological properties of the compound. The ordering of the various chemical reactions that occur during cyanobactin biosynthesis is not fully understood. The structure of the flavin-dependent enzyme responsible for the oxidation of multiple thiazolines reveals it contains an additional domain that in other enzymes recognizes linear peptides. We characterize the activity of the enzyme on two substrates: one with a peptide leader and one without. Kinetics and biophysics reveal that the leader on the substrate is not recognized by the enzyme. The enzyme is faster on either substrate than the macrocyclase or protease in vitro. The enzyme has a preferred order of oxidation of multiple thiazolines in the same linear peptide.